Performance Analysis of Full Assembly Glass Fiber-Reinforced Polymer Composite Cross-Arm in Transmission Tower - Syamsir A.; Nadhirah A.; Mohamad D.; Beddu S.; Muhammad Asyraf M.A.R.; Itam Z.; Anggraini V. (MDPI, 2023)
Electric power transmission; Fiber reinforced plastics; Glass fibers; Load testing; Reinforcement; Safety factor; Towers; Transmissions; Wire; Wood; Broken wires; Condition; Cross arm; Finite element analyse; Glass-fiber reinforced polymer composites; Glassfiber reinforced polymers (GFRP); Performances analysis; Pultruded composites; Transmission tower; Working loads; Finite element method